Burkitt's lymphoma in Greek adults - A study of the Hellenic co-operative oncology group - Economopoulos, T.; Dimopoulos, M.A.; Foudoulakis, A.; Nikolaidis, C.; Tsatalas, C.; Pectacides, D.; Rontogianni, D.; Papageorgiou, E.; Fountzilas, G. (Leukemia Research, 2000)
Non-African Burkitt's lymphoma is a rare disease among adults without AIDS. Among 1352 Greek adult patients with non-Hodgkin's lymphoma, 24 cases (1.8%) were classified as Burkitt's (BL) or Burkitt-like (BLL) lymphoma. Eleven cases fulfilled the criteria of BL and 13 of BLL. No statistical differences were found in the general characteristics of the two groups at the time of diagnosis. Extranodal involvement was a common finding in both groups and bulky disease (> 10 cm) was observed in almost one half of the patients. The majority of the patients were treated with intensive, although different, protocols. After induction treatment, complete remission (CR) was achieved in 14 patients (60.8%). CR was reached in all cases with stage I-II, while in stage IV the CR rate was 30.4%. The median overall survival was 27 months. The median survival for BL was 13 months compared to 27 months in the BLL group (P = 0.34). The data of the present retrospective analysis, indicated that there were not significant clinical differences between BL and BLL variants. Since BLL is still a non-reproducible category in the REAL classification, all BL variants must be treated uniformly with intensive protocols. (C) 2000 Elsevier Science Ltd.
Keywords: Adults; Burkitt's; Burkitt-like lymphoma; Clinical characteristics